An Analysis Of Jargons Used By The Housekeeping Department At The Lovina Bali Hotel - Ni Luh Aristyawati; I Gede Budasi; Nyoman Karina Wedhanti (Universitas Pendidikan Ganesha, 2020)
This study aimed to 1) identify the jargons used, 2) analyze the word formations process, 3) explain the meaning of each jargons used by the Housekeeping Department at The Lovina Bali Hotel. Jargons is analyzed respectively based on the theories of Allan and Burriged (2006), Yule's theory (2006) and Hornby's theory (1995). This study was descriptive qualitative research. The subjects of this study were the 3 Housekeeping staff. The instruments that are used in this study were checklist, tape recorder, interview guide. This study found 104 jargons and showed that there are 8 types of word formation appears in this study, in the terms of phrases (46 or 4.23%), abbreviations (37 or 35.57%), nouns (4 or 3.84%), verbs (2 or 1.92%), borrowing (2 or 1.92%), backformations (2 or 1.92%), adjectives (1 or 0.96%), derivation (1 or 0.96%), and clippings (1 or 0.96).